EVALUATION OF SUCCESSFUL IMPLEMENTATION OF LOCAL FINANCIAL MANAGEMENT INFORMATION SYSTEM (LFMIS) SUTDY AT YOGYAKARTA MUNICIPAL GOVERNMENT - Ignatius Novianto Hariwibowo (ABIS: Accounting and Business Information Systems Journal, 2013)
This study aimed to evaluate the success of the implementation of the Municipal Government LFMIS in Yogyakarta. LFMIS success will be evaluated using the model of DeLone and McLean (2003) by adding variables to the model hopes to complement the less variable in the model of DeLone and McLean (2003). Cognitive dissonance theory (cognitive dissonance theory) explains that the perception or performance will change to reflect the expectations. In the application of the system, while a system is forced to conform to the requirements, it can degrade the performance of the system for use in a control system can be ignored . In addition, the expectation confirmation theory (expectation confirmation theory) suggests that when expectations match the reality it would appear involvement or support for the implementation of systems that impact on the successful implementation of the system . The results of this study indicate that LFMIS successfully applied in the Municipal Government of Yogyakarta. This was indicated by the net benefits provided LFMIS the municipal government of Yogyakarta.